A self-propelling endoscopic system - Lim, YM; Lee, J; Park, J; Kim, B; Park, JO; Kim, SH; Hong, YS (IROS 2001: PROCEEDINGS OF THE 2001 IEEE/RJS INTERNATIONAL CONFERENCE ON INTELLIGENT ROBOTS AND SYSTEMS, VOLS 1-4: EXPANDING THE SOCIETAL ROLE OF ROBOTICS IN THE NEXT MILLENNIUM, 2001)
The existing colonoscope requires a dexterous skill of surgeon to perform the insertion in entire colon. The procedure is painful to the patient. Therefore, biomedical and robotic researchers are developing a locomotive colonoscope that can travel safely, in colon. In this paper, we describe a new design and concept of semi-autonomous micro robot for colonoscopy. The micro robot comprises the actuation system, bow-shaped flexible supporters to keep the space between colon wall and the actuator, camera and LED for diagnosis and steering system to pass through the acute angle in colon. We suggest two actuating methods. One is based on the reaction force, and the other is impact force. For the performance test, the preliminary experiments are carried out in rigid pipe to validate the concept.